ELASTISITAS PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN SUMENEP - Rasid, Karman; waluyo, Dw Eko (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2012)
The research is quantitative descriptive research from 2005/2006- 2008/2009, and this research uses non-participant observation. The research purpose is to find out how large regional original income elasticity to Regional Gross Domestic Product in range time 2005/2006- 2008/2009 also to find out how large task and retribution elasticity to Sumenep Regency Gross Domestic Product. Research result from 2005/2006- 2008/2009 shows: (1) Regional Original Income elasticity to Regional Gross Domestic Product of Sumenep Regency has average 1,84 %, (3) Retribution elasticity to Sumenep Regency Regional Gross Domestic Product average is 1,79 %, (4) Regional Original Income elasticity to the amount of Sumenep Regency inhabitants amount has average 310,56 %, (5) Task elasticity to the amount of Sumenep Regency inhabitants has average 707,13 %, and (6) Retribution elasticity to average inhabitants amount is 797,13 %. From equation above, it can be concluded that regional original income to Regional Gross Domestic Product of Sumenep Regency is quite sense from year 2005/2006- 2008/2009, that?s why it needed to be defended. While the suggestion is improving regional economic growth and add retribution and tax objects also intensification of retribution and task payment system.